2014
DOI: 10.1108/ijoa-10-2011-0520
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between transformational leadership behaviors and manufacturing strategy

Abstract: Purpose – It is widely agreed that top management's leadership behavior is a source for achieving and sustaining competitive advantage. Very few research studies analyzed the prevalence of transformational leadership style in the manufacturing environment, and importantly, the associations between transformational behaviors and manufacturing strategies in connection with flexibility, quality, delivery, and cost are not yet deeply explored in the literature. In this direction, efforts are initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 75 publications
1
28
0
2
Order By: Relevance
“…If the AVE for each construct exceeds the square correlation between that construct and any other constructs then discriminant validity is occurred (Fronell and Larcker, 1981). As shown in Table 5, this study showed that the AVEs of all the constructs were above the suggested level of 0.50, implying that all the constructs that ranged from 0.54 to 0.71 were responsible for more than 50 percent of the variance in their respected measurement items, which met the recommendation that AVE values should be at least 0.50 for each construct (Bagozzi and Yi, 1988;Holmes-Smith, 2001). Furthermore, as shown in Table 6, discriminant validity was confirmed as the AVE values were more than the squared correlations for each set of constructs.…”
Section: Content Convergent and Discriminant Validitysupporting
confidence: 54%
See 1 more Smart Citation
“…If the AVE for each construct exceeds the square correlation between that construct and any other constructs then discriminant validity is occurred (Fronell and Larcker, 1981). As shown in Table 5, this study showed that the AVEs of all the constructs were above the suggested level of 0.50, implying that all the constructs that ranged from 0.54 to 0.71 were responsible for more than 50 percent of the variance in their respected measurement items, which met the recommendation that AVE values should be at least 0.50 for each construct (Bagozzi and Yi, 1988;Holmes-Smith, 2001). Furthermore, as shown in Table 6, discriminant validity was confirmed as the AVE values were more than the squared correlations for each set of constructs.…”
Section: Content Convergent and Discriminant Validitysupporting
confidence: 54%
“…Table 5 indicates that all Cronbach Alpha values for the eight variables exceeded the recommended value of 0.60 (Bagozzi and Yi, 1988) demonstrating that the instrument is reliable. Furthermore, as shown in Table 5, composite reliability values ranged from 0.85 to 0.96, and were all greater than the recommended value of more than 0.60 (Bagozzi and Yi, 1988) or greater than 0.70 as suggested by Holmes-Smith (2001). Consequently, according to the above two tests, all the research constructs in this study are considered reliable.…”
Section: Reliabilitymentioning
confidence: 66%
“…Even when taking into account the combined leadership styles, the results of these studies are still inconclusive with respect to which styles are effective for entrepreneurs and which styles have positive effect on TQM practices. Birasnav (2014) investigated the link between transformational leadership behaviors and manufacturing strategies and found that transformational leaders ensure quality at all stages of production process and support and delivery process. Although some of the previous studies focused on a single leadership style, particularly transformational leadership, as pertinent in the implementation of TQM, these studies were not able to give a comprehensive answer to the question of how entrepreneurial leadership style impact TQM practices.…”
Section: Entrepreneurial Leadership and Tqm Practicesmentioning
confidence: 99%
“…VonKrogh et al, (2012), indicated that transactional leadership focuses on leader-follower exchanges, rewards and exceptions, on the other hand, focuses on inspiration, stimulation and motivation. Birasnav (2014), suggest that transformational leadership is superior to transactional leadership. Whereas, Yukl (2012) claims that different leadership styles are useful in different environments and organizations; situational variables can determine the relevant behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%